Driftodontics and Its Role in Orthodontics: A Clinical Study on 40 Patients at Military Dental Centre Dhaka: A Clinical Study on 40 Patients at Military Dental Centre Dhaka: Driftodontics and Its Role in Orthodontics - Sheikh, Md Asaduzzaman; Asharaf, Arefin; Sinha, Susmita (Journal of the Medical College for Women & Hospital, 2025)
Background: Driftodontics has emerged as a promising approach that leverages the natural physiological movement of teeth to achieve alignment. This concept involves creating optimal conditions—such as through selective extractions, interproximal reduction, or occlusal adjustments—to guide teeth into their ideal positions without the need for extensive mechanical appliances. Objective: To evaluate the clinical efficacy of Driftodontics—a minimally invasive orthodontic approach leveraging natural tooth drifting—compared to traditional orthodontics in patients with mild-to-moderate malocclusions.Materials and Method: A 24-months prospective observational study was conducted at the Military Dental Centre Dhaka on 40 patients (aged 18–35 years). Participants were divided into two groups: Driftodontics (selective extractions, interproximal reduction; n=20) and Traditional Orthodontics (fixed appliances; n=20). Outcomes included alignment success, treatment duration, patient satisfaction, and occlusal stability. Results: Driftodontics achieved 85% alignment success versus 95% with traditional methods (p=0.16), with significantly shorter treatment duration (8.2 vs. 14.6 months; p<0.001). Patient satisfaction was higher in the Driftodontics group (90% vs. 65%; p=0.04). Both groups showed comparable occlusal stability (PAR score reduction: 82% vs. 88%; p=0.32). Conclusion: Driftodontics offers a time-efficient, patient-friendly alternative for mild-to-moderate malocclusions, particularly in time-constrained populations, without compromising clinical outcomes. J Med Coll Women Hosp.2025; 21 (2):78-82